Zur spät- und postglazialen Reliefformung auf der nördlichen Varangerhalbinsel (Nord-Norwegen) - Gießübel, Jürgen (ERDKUNDE, 1984)
The north coast of the Varanger Peninsula is characterised by fluvio-glacial deposits in valley mouths and sea bays. Raised shore lines allow the dating of these sediments as late- and post-glacial. Boulder-rich moraines and sorted polygons with recent frost heaved forms can be found. The slopes are covered with gelifluction material, on lower parts gelifluction lobes are presently active.Various rates of podsolization occur in the different materials. This paper reveals formation by wind during the whole late- and post-glacial period as well as recent formation of dunes and blow outs near the coastline, but more than this, it proves that periglacial morphodynamics with permafrost were only possible for a short time under local climatic conditions at the beginning of the late glacial period. It seems that a hypsometric differentiation of forms already started at the north coast of Varanger Peninsula before the Dryas, so that we cannot speak of a periglacial area in the strict sense of the term. The Varanger Peninsula with its fossil and partly active periglacial forms contains features characteristic of three different morphodynamic zones: the subarctic periglacial zone, the former periglacial zone like Europe and the periglacial belt of high mountains. The spreading of periglacial forms during the late and post glacial period is caused by local conditions. For that reason they alone are not sufficient for the reconstruction of climatic or geomorphic developments in different far away-areas.